Use of Fantasy in J.M. Coetzee’s The Heart of the Country: A Critical Study - Dr. Paresh N. Jotangiya (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
It was only recently that fantasy emerged as a distinct genre. It was viewed as a subpar component of science fiction writing for a very long period. Fantasy's long literary history may be linked to ancient mythology, stories, folklore, and carnival art. Thus, it may be claimed that fantasy once belonged to another genre before evolving into its own. With the advent of chivalric novels, epic fantasy became a tradition. According to Carter, the fantasy genre's genuine origins may be found in the nineteenth century, when it first developed in response to society's industrialization. This essay examines Coetzee's book The Heart of the Country to see how he employs imagination in his works.